USING WORD LIST ON THE WORD WALL STRATEGY ON STUDENTS’VOCABULARY LEARNING RESULT - Sri Marina Ulfa; Azizah NA (Lingua, 2017)
This research principally aims to investigate whether or not word list on the word wall significantly affects students’ vocabulary learning result. The research samples were taken using cluster random sampling, with the total number of samples being 70 students. The location of this research was SMPN 198 Jakarta. The research methodology adopted was quasi-experiment method with the research design being posttest only control group design. To collect the data, the students were given objective test, numbering 50 items. The research data were analyzed by using ONE-WAY ANOVA. The findings indicated that there was significant difference of post-test score between the students who received Word List Word Wall Strategy and students who did not receive Word List on the Word Wall. The writer found the significant level (Sig) in line with the ANOVA statistic was 0.000 which was lower than 0.05 means that Ho is rejected and Ha is accepted.it means that Word List on the Word Wall Strategy has significant effect on students’ vocabulary learning result.